Managerial ideology and identity in the nationalised British coal industry, 1947–1994. (February 2023) - Perchard, Andrew; Gildart, Keith
This article examines managerial ideology and identity in the nationalised British coal industry. On nationalisation in 1947, the National Coal Board (NCB) – after 1987 the British Coal Corporation – became the largest socialised industry outside of the Communist bloc. Privatised in 1994, as part of liberal market reforms, the industry was a crucible for ideological clashes amongst managers. The article responds to interest in the impact of managerial ideologies and identities on organisations and in the search for illuminating historical case studies in different organisational settings. The authors position those ideological clashes, and distinctive managerial identities, within a moral economic framework.